The importance of learning styles and strategies - Provics Andrea (2006)
My aim is to highlight the importance of learning styles and learning strategies. I want to prove that students who are going to be teachers in a year or two are well informed in this topic and they know how to develop their students' study skills. But the results of the questionnaires show another picture. Students do not know enough about learning styles and they think that it is not the teacher who is responsible for developing children's learning strategies and study skills.